1990
DOI: 10.1128/mcb.10.7.3386
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of I-Ppo, an intron-encoded endonuclease that mediates homing of a group I intron in the ribosomal DNA of Physarum polycephalum.

Abstract: A novel and only recently recognized class of enzymes is composed of the site-specific endonucleases encoded by some group I introns. We have characterized several aspects of I-Ppo, the endonuclease that mediates the mobility of intron 3 in the ribosomal DNA of Physarum polycephalum. This intron is unique among mobile group I introns in that it is located in nuclear DNA. We found that I-Ppo is encoded by an open reading frame in the 5' half of intron 3, upstream of the sequences required for self-splicing of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 36 publications
1
83
0
Order By: Relevance
“…I-PpoI's recognition sequence is found in the coding region of the 28S ribosomal DNA (rDNA) sequence, which is tandemly repeated at 5 chromosomal loci (30), as well as in intron 1 of the DAB1 gene on chromosome 1 (7). The enzyme produces about 20 to 30 DSBs per cell (20,60). Using this system and others, ␄H2Ax has been shown by chromatin immunoprecipitation (ChIP) to be present up to a megabase away from the break site but absent from the actual break site and regions in close proximity to the break.…”
Section: Resultsmentioning
confidence: 99%
“…I-PpoI's recognition sequence is found in the coding region of the 28S ribosomal DNA (rDNA) sequence, which is tandemly repeated at 5 chromosomal loci (30), as well as in intron 1 of the DAB1 gene on chromosome 1 (7). The enzyme produces about 20 to 30 DSBs per cell (20,60). Using this system and others, ␄H2Ax has been shown by chromatin immunoprecipitation (ChIP) to be present up to a megabase away from the break site but absent from the actual break site and regions in close proximity to the break.…”
Section: Resultsmentioning
confidence: 99%
“…We have no evidence for internal sites of telomeric sequences as found in chromosome III of yeast (Oliver et al 1992). However, cleavage of intact Giardia chromosomes with the intron-specific endonuclease, I-PpoI (Muscarella et al 1990), which also cleaves a 15-bp recognition site in the Saccharomyces cerevisiae rDNA sequence (Lowery et al 1992) and a number of other rDNA sequences, including Giardia (P. Upcroft, unpubl. ), removes all rDNA arrays.…”
Section: Rearrangements and Recombination Within The Rdna Unitsmentioning
confidence: 99%
“…Group I introns are phylogenetically widespread autocatalytic RNA elements sharing a common secondary and tertiary structure (Cech et al+, 1994)+ Many group I introns are capable of self-splicing in vitro through a series of transesterification reactions (Cech, 1990), although proteins may aid splicing in vivo (Lambowitz & Perlman, 1990;Shaw & Lewin, 1997)+ About one third of group I introns harbor open reading frames (ORFs) coding for either structural proteins, maturases, or DNA endonucleases (Johansen et al+, 1997a)+ The DNA endonucleases, which are the most common intron-encoded proteins, are usually involved in intron mobility at the DNA level (reviewed in Belfort & Roberts, 1997)+ The endonuclease creates a doublestrand break at the intron-lacking allele, which is subsequently repaired in a gene-conversion event, using the intron-containing allele as a template+ The resulting unidirectional transfer of intron sequences is termed intron homing because of its high specificity at a homologous site+ Only 5% of the ;300 reported nuclear rDNA group I introns contain ORFs, and among these are the optional PpLSU3 and DiSSU1 of the myxomycetes Physarum polycephalum and Didymium iridis, respectively (Muscarella & Vogt, 1989;Johansen & Vogt, 1994), and NaSSU1 in a few species of the free-living amoebaflagellate Naegleria (De Jonckheere, 1994)+ These introns interrupt rRNA genes on extrachromosomal rDNA molecules (see Einvik et al+, 1998a), and encode the functional site-specific His-Cys box homing endonucleases named I-PpoI, I-Dir I, and I-NjaI, respectively (Muscarella et al+, 1990;Johansen et al+, 1997b;Elde et al+, 1999)+ I-PpoI and I-Dir I are involved in homing in their natural hosts after mating (Muscarella & Vogt, 1989;Johansen et al+, 1997b)+ NaSSU1 and DiSSU1 constitute a unique class of group I introns referred to as twin-ribozyme group I introns (Decatur et al+, 1995;Einvik et al+, 1997Einvik et al+, , 1998a)+ In these introns, the endonuclease ORF is found downstream of a small group I self-cleaving ribozyme (GIR1) that catalyzes hydrolytic cleavage of the RNA just upstream of the endonuclease ORF (see Fig+ 1)+ These two elements are both embedded in a loop of a more regular group I self-splicing ribozyme (GIR2)+ Strikingly, some species of Naegleria contain a shorter version of NaSSU1 that lacks both the ORF and GIR1 (De Jonckheere & Brown, 1994;Einvik et al+, 1997), suggesting that these two elements form a functional genetic unit, acquired or lost at the same time in evolution+ Despite their small si...…”
Section: Introductionmentioning
confidence: 99%